PEMBEBASAN TANAH GARAPAN UNTUK PROYEKPEMBANGUNAN LIGHT RAIL TRANSIT STUDIPUTUSAN NOMOR 45/PDT.G/2021PN-CKR: Land Acquisition for Light Rail Transit Development Project: Study of Decision Number 45/Pdt.G/2021/PN-CKR - Azzahra Sahda; Intan Nevia Cahyana (Faculty of Law, Universitas Trisakti, 2025)
The determination of the Entitled Party in the Land Acquisition Implementation phase basically refers to the provisions of Law Number 2 of 2012 concerning Land Acquisition for Public Purposes, supported by other related regulations such as Government Regulation Number 19 of 2021 on the Implementation of Land Acquisition for Public Development Purposes. It is emphasized that the Entitled Party is the one who truly has valid proof of ownership and/or legitimate control that can be accountable for its accuracy. Therefore, at the identification stage to determine the subject and object. The identified problem in this study is how the determination of entitled parties in the implementation stage of land acquisition is carried out in accordance with statutory regulations. The land acquisition implementer must thoroughly consider both the physical and juridical aspects of ownership of the land affected by the alignment for the Light Rail Transit (LRT) development in the Jabodetabek area. Based on the results and conclusion of the study, it is concluded that the provisions regarding the entitled parties are crucial to ensure legal certainty and avoid ownership disputes, as well as to provide a solid legal basis in every stage of land acquisition implementation, especially in national strategic infrastructure projects such as Jabodetabek LRT.